2017
DOI: 10.1164/rccm.201709-1858st
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Research Priorities for Smoking Cessation Interventions within Lung Cancer Screening Programs. An Official American Thoracic Society Research Statement

Abstract: Rationale: Smoking cessation counseling in conjunction with low-dose computed tomography (LDCT) lung cancer screening is recommended in multiple clinical practice guidelines. The best approach for integrating effective smoking cessation interventions within this setting is unknown. Objectives: To summarize evidence, identify research gaps, prioritize topics for future research, and propose standardized tools for use in conducting research on smoking cessation interventions within the LDCT lung cancer screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Screening should not be viewed as an alternative to smoking cessation. In this clarification and update, the importance of smoking‐cessation counseling is more clearly stated as an important element of the process of identifying high‐risk adults who are eligible for lung cancer screening …”
Section: Screening For Lung Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Screening should not be viewed as an alternative to smoking cessation. In this clarification and update, the importance of smoking‐cessation counseling is more clearly stated as an important element of the process of identifying high‐risk adults who are eligible for lung cancer screening …”
Section: Screening For Lung Cancermentioning
confidence: 99%
“…In this clarification and update, the importance of smoking-cessation counseling is more clearly stated as an important element of the process of identifying high-risk adults who are eligible for lung cancer screening. [96][97][98] This clarification properly places the emphasis as intended on a positive recommendation for screening based on randomized trial evidence of screening efficacy in reducing lung cancer mortality and a judgment that the balance between potential benefits and harms is favorable. The recommendation continues to affirm the necessary conditions of appropriate selection of individuals to be screened, an opportunity for each patient to be provided information and to gain an understanding of the screening process and possible outcomes, and access to high-quality screening and follow-up (Table 5).…”
Section: Screening For Lung Cancermentioning
confidence: 99%
“…A collaborative statement on current chronic obstructive pulmonary disease (COPD) research needs, published by the ATS and the European Respiratory Society, positions pretreatment in pursuit of smoking reduction as a potential mechanism for reducing COPD respiratory symptoms but does not address the potential role of pretreatment for all patients with COPD who continue to smoke ( 144 ). The ATS research statement on smoking-cessation interventions in lung cancer screening programs identified the profound drop-off in intervention rates after assessment of quit readiness as a potential point for performance improvement but did not make specific pretreatment recommendations ( 145 ). The Canadian Cancer Society produced an educational flyer encouraging agency among smokers not ready to quit ( 146 ).…”
Section: Questions and Recommendationsmentioning
confidence: 99%
“…[82][83][84] While addressing smoking cessation in the setting of lung cancer screening in the United States is required by the Centers for Medicare and Medicaid Services, widely recommended by national preventive health experts and other related professional organizations and societies, best practices for integration and implementation of evidence-based tobacco treatment in the context of lung cancer screening are not well defined. 81,85 Data from the larger lung cancer screening trials have shown mixed results with regard to the impact of screening on smoking habits. NELSON data suggested a possible negative impact on smoking as screening was associated with a lower prolonged abstinence rate compared to the control group (14.5% versus 19.1%; odds ratio ¼ 1.40, 95% CI: 1.01-1.92; p < 0.05).…”
Section: Screening and Smoking Cessationmentioning
confidence: 99%